DINAMIKA PENDIDIKAN ISLAM TRADISIONAL PADA MASA KEJAYAAN ANDALUSIA - Munzirin, Al (NIHAYAH: Journal of Islamic Studies, 2025)
This study explores the dynamics of traditional Islamic education during the golden age of Andalusia as a unique and progressive model of intellectual civilization. The main focus of the research is to examine the educational institutions, integrated curricula, and the contributions of prominent Muslim scholars in shaping a scientific tradition that had a significant influence on European intellectual development. Employing a qualitative historical approach, this study analyzes both primary and secondary sources, including historical manuscripts, contemporary scholarly works, and academic literature published between 2018 and 2025. The findings reveal that the Andalusian Islamic education system emphasized the integration of mosques, madrasahs, and libraries as key centers of scholarly activity. The curriculum developed in Andalusia was interdisciplinary in nature, blending religious sciences with rational sciences, and fostering a culture of intercultural and interfaith intellectual exchange. This model of education led to the emergence of influential figures such as Ibn Rushd, Ibn Tufail, and Al-Zahrawi, who played crucial roles in transmitting knowledge to the West. Furthermore, the Andalusian educational legacy significantly contributed to the rise of European intellectual movements, especially during the Renaissance. The study also highlights the relevance of Andalusia's educational values in the context of modern Islamic education, particularly in promoting knowledge integration, tolerance, and lifelong learning. These findings enrich the discourse on Islamic educational heritage and offer important insights for reformulating inclusive and future-oriented curricula in contemporary Islamic education.